Successful Resolution of a Large Left Atrial and Left Atrial Appendage Thrombus with Rivaroxaban - Safwan Gaznabi; Ashraf Abugroun; Hasan Mahbub; Enrique Campos (Case Reports in Cardiology)
A 79-year-old male was admitted to the hospital for acute exacerbation of heart failure. The patient had history of atrial fibrillation and was planned for cardioversion. Preprocedure transesophageal echocardiogram (TEE) revealed a large multilobulated mobile thrombus in the left atrial appendage. The patient refused warfarin therapy and instead chose to take rivaroxaban. Upon outpatient follow-up, 3 months later, no visible thrombus was appreciated on repeat TEE. This case demonstrates successful resolution of left atrial and left atrial appendage thrombi with the use of rivaroxaban. At present time, limited data is available to support the use of rivaroxaban for treatment of intracardiac thrombi. This case highlights the need for further studies to investigate the outcomes and relative efficiency of use of direct oral anticoagulants (DOACs) in lysis of intracardiac thrombus. The benefits of DOACs compared to the standard of therapy could increase patient compliance, reduce length of stay, and improve treatment efficacy.